Results of type testing of MTS-N dosimeters with IEC 62387:2012 standard at the laboratory of external dosimetry in Nicaragua - Andrea Castillo; Norma Roas (Brazilian Journal of Radiation Sciences, 2022)
This study presents the results of the verification of the method according to working procedures of the Laboratory of External Dosimetry (LDE) located at the Laboratory of Radiation Physics and Metrology (LAF-RAM), which is the only Individual Monitoring service provider in Nicaragua. The test is considered as validation of the method since the LAF-RAM follows a Quality Management System. The chosen performance testing according to IEC 62387:2012 are Coefficient of variation, Non linearity, Radiation energy and angle of incidence, Dosimeter droop, Light exposure (reader), Over-response of radiation incidence and Build up, fading, self-irradiance and natural radiation response. The results in general show that all test are in compliance with the requirements except for some temporal conditions in Buildup, fading, self-irradiance test.